POLITICAL CULTURE OF MODERN TURKEY - Rakhimberdiyev, М.М.; Shadkam, З. (Journal of Oriental Studies, 2025)
The political culture of modern Turkey reflects a dynamic interplay between the Ottoman heritage and modern European influences. This combination creates a peculiar balance between tradition and transformation. At the beginning of the republican era, Turkey's political culture was shaped by both internal developmental aspirations and external pressure from international organisations. The establishment of the republic marked a decisive shift towards secularism and modernisation, but the influence of tradition remained steady. With the rise to power of R. T. Erdoğan, this balance changed. His period in power represents a new phase characterised by the centralisation of power, which has caused discontent among both religious and secular sectors of society. This phase deepened the political polarisation between these groups. Religion has become a more significant unifying force than Turkish nationalism, and Muslim identity acts as a bridge between different social classes. Socio-political issues such as the Syrian refugee crisis and economic instability have further influenced Turkey's political culture, causing shifts in political awareness and engagement. These problems have increased the politicisation of society, revealing the interconnectedness of economic and social problems with political attitudes. The article examines the above dynamic interactions of factors contributing to the distinctiveness of Turkish political culture and emphasises the crucial role of religion, socio-political issues in shaping the contemporary political landscape. The methodology used includes analyses of historical events, discourse analysis of political rhetoric and the study of socio-political trends using recent developments in the region under study as examples. Keywords: ideology, national identity, political culture, Turkey, 20th and 21st centuries.